ANALISIS LIKUIDITAS DAN PERPUTARAN MODAL KERJA DI PT. SARIGUNA PRIMATIRTA TBK. - Rina Masithoh Haryadi, Putri Anggun Astriani Titin Ruliana 2 (EKONOMIA, 2021)
The purpose of this study is to determine and analyzeCapital Turnover                           the Capital Turnover effect of liquidity levels on working capital turnover at PT. Sariguna Primatirta Tbk. period 2017-2019.                                                    This study uses analysis tools Qurrent Ratio, Quick Ratio, Cash Ratio and Working Capital Turnover. Current ratio is known by comparing current assets consisting of cash, accounts receivable and inventories with current accounts payable. Quick ratio can be found by comparing current assets after deducting inventory divided by current debt. Cash Ratio). Meanwhile, the cash ratio compares the company's total cash and cash equivalents to its current debt. Turnover of working capital is the frequency of that capital turnover in a certain period or is a comparison between the amount of sales on the one hand and working capital on the other.                                                    Based on the results of research, analysis and discussion of "Analysis of Liquidity and Working Capital Turnover at PT. Sariguna Primatirta Tbk. " shows that the increase in liquidity of PT. Sariguna Primatirta Tbk. 2017-2019 was not fully followed by an increase in working capital turnover. Increasing liquidity will reduce the company's working capital turnover. Likewise, the decrease in liquidity will increase the company's working capital turnover. The increase in the rate of working capital turnover was due to the increase in sales which was greater than the increase in working capital.